2020
DOI: 10.21203/rs.3.rs-17635/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk of rebleeding from gastroesophageal varices after initial treatment with cyanoacrylate: a systematic review and pooled analysis.

Abstract: Background Cyanoacrylate alone or in combination with other interventions, can be used to achieve variable rates of successes in preventing rebleeding. Our study aims to assess the pooled risk of gastric and esophageal varices rebleeding after an initial treatment with cyanoacrylate alone and/or in combination with other treatments, by systematic review of literature and pooled analysis.Methodology PubMed, EMBASE, SCOPUS and the Cochrane library were searched for studies that reported the risk of rebleeding du… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Two more recent systematic reviews/meta-analyses have reported similar results. Hu et al, after correcting for study heterogeneity, reported that, when gastric varices were treated with cyanoacrylate alone (n = 309), the risk of rebleeding was 15 % (95 %CI 11 % to 18 %) 108 . Chirapongsathorn et al included seven RCTs (n = 583) comparing endoscopic injection of N‐butyl‐2‐cyanoacrylate glue with any other treatment approach not involving cyanoacrylate (propranolol only, EBL, or sclerotherapy with alcohol or ethanolamine).…”
Section: Endoscopic Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Two more recent systematic reviews/meta-analyses have reported similar results. Hu et al, after correcting for study heterogeneity, reported that, when gastric varices were treated with cyanoacrylate alone (n = 309), the risk of rebleeding was 15 % (95 %CI 11 % to 18 %) 108 . Chirapongsathorn et al included seven RCTs (n = 583) comparing endoscopic injection of N‐butyl‐2‐cyanoacrylate glue with any other treatment approach not involving cyanoacrylate (propranolol only, EBL, or sclerotherapy with alcohol or ethanolamine).…”
Section: Endoscopic Managementmentioning
confidence: 99%
“…Several systematic reviews/meta-analyses have evaluated the efficacy of cyanoacrylate injection for the treatment of GVH 105 106 107 108 109 . Qiao et al reported on three RCTs, which included 194 patients with active gastric variceal bleeding, comparing endoscopic cyanoacrylate injection versus EBL 106 .…”
Section: Endoscopic Managementmentioning
confidence: 99%
“…BL or rubber-band ligation represents one of the oldest techniques in the treatment of gastrointestinal varices [8]. It is inferior to cyanoacrylate injection and embolization coils in terms of the overall success rate and rebleeding risk [3]. However, BL is cost-effective, less technically demanding than the aforementioned techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Oesophageal varices result from portal hypertension as a frequent manifestation of liver cirrhosis [1]. About 60%-80% of liver cirrhosis patients develop gastrointestinal varices, with oesophageal varices constituting 17% [2,3]. The frequency of developing oesophageal varices is rmly attributed to the severity of liver disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation